2011
DOI: 10.1007/s00420-011-0640-9
|View full text |Cite
|
Sign up to set email alerts
|

The mediating and moderating role of personal strain and coping resource in the relationship between work stressor and quality of life among Chinese nurses

Abstract: Personal strain and coping resources have both mediating and moderating effects on the relationship between work stress and quality of life in a sample of Chinese nurses. An effective intervention strategy is needed to reduce work stress and ensure better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…The degree of insulin resistance and β-cell function in each participant was estimated using homeostasis model assessment of Matthews method (Matthews et al 1985). The comparative fit index (CFI), goodness of fit index (GFI), adjust goodness of fit index (AGFI), and root-mean-square residual (RMR) were used to assess the model fit (Wu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of insulin resistance and β-cell function in each participant was estimated using homeostasis model assessment of Matthews method (Matthews et al 1985). The comparative fit index (CFI), goodness of fit index (GFI), adjust goodness of fit index (AGFI), and root-mean-square residual (RMR) were used to assess the model fit (Wu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have explored HRQOL found that the presence of work stress resulted in burnout or personal strain and had a negative effect on nurses' HRQOL. 12,17 Presence of satisfactory work ability, on the other hand, had a positive effect on nurses' HRQOL. 32 Even so, at least in some countries, nurses' HRQOL was relatively low.…”
Section: Nursing Is a Meaningful Occupationmentioning
confidence: 97%
“…Based on a literature review and existing knowledge, this study hypothesized that RONC acts as mediator in the relationship between nurse staffing and patient outcomes. To clarify the meaning of the mediation effect, a path diagram is used as a model for depicting a basic causal chain involved in mediation [18].…”
Section: Introductionmentioning
confidence: 99%